CAPITAL MARKETâS REACTION TOWARDS 2014 WORKING CABINET ANNOUNCEMENT (INDONESIAN CASE STUDY) - Ardiansari, Anindya; Saputra, Arif (Department of Management, Faculty of Economics, Semarang State University, Indonesia, 2015)
The purpose of this study is to examine the market reaction regarding the announcement Â of working cabinet following the election of Jokowi as the President of Indonesia. Political events such as presidential election, government change, cabinet announcement, and other events are very influential towards price and trade volume at the stock exchange since the political events are closely related to the state economy stability. Â The Sample in this study is stock which was listed as issuers in Indonesia Stock Exchange (IDX) which included in LQ45 company group during this research period from 20 Octoberâ 3 November 2014. The result shows that there was significant effect towards abnormal return difference before and after the cabinet announcement on the companies listed in LQ 45. The existence of this significant difference means that market reacted with the cabinet announcement event.